The effect of preoperative fasting on the water sectors of the body in the perioperative period in children - Yu. S. Aleksandrovich; K. V. Pshenisnov; Sh. Sh. Shorakhmedov; G. P. Tihova (Вестник анестезиологии и реаниматологии, 2024)
Introduction. Avoiding solid foods and liquids before surgery is a common practice in elective surgery in pediatric, however, there is a risk of dehydration.The objective was to assess the distribution of fluid across the water sectors of the body in children according to the duration of refusal of food and liquids before elective surgery.Materials and methods. A single-center prospective cohort study. 104 children were examined, the average age was 12.5 ± 3.7 years. Depending on the age, patients were divided into three groups: group I: 3–7 years old, group II: 7–12 years old and group III: 12–18 years old. In each group, taking into account the duration of preoperative refusal of food and fluid, there were two subgroups: subgroup I – less than 12 hours; subgroup II – more than 12 hours. The average fasting time was 13.3 ± 2.7 hours. The condition of the water sectors of the body was assessed 30 minutes before surgery, 30 minutes and 24 hours after surgery.Results. Before the operation, the distribution of fluid across the water sectors in groups I and II, depending on the duration of fasting, did not differ; in group III, when fasting for more than 12 hours, all indicators were significantly lower. 30 minutes and 24 hours after the intervention, an increase in the volume of total water and extracellular fluid was observed, however, significant changes were only in group III (p < 0.05). In group III, when fasting for more than 12 hours before surgery, lower systolic BP values were observed (p < 0.05).Conclusion. The duration of preoperative refusal of solid food and liquids in the range of 12–15 hours does not adversely affect the indicators of water metabolism and is not associated with arterial hypotension during the induction of anesthesia.